(untitled) (Conference Zone, 2022)
The creativity and ideological postulates of Navoi were seriously influenced by Sufi literature, especially the works of such representatives of tasawwuf as Anvari, Hafiz, Saadi, Nizami, Dehlavi, Jami. We argued the truth that Navoi singled out from a large number of Sufis those who preached sincere love for both Allah and man, who combined religious and secular, earned a living by their work. A special role in the life of Navoi was played by Nizami Ganjavi, Khosrav Dehlavi and Abdurakhman Jami - his predecessors and teachers in the creation of «Khamsa».